Setting up a long-term research project for economics at the Cowles Commission: The definition of theory as a mathematically and abstractly driven form of knowledge - Camila Orozco Espinel (Duke University, Center for the History of Political Economy (CHOPE), 2019)
This paper offers an analysis of the challenges the researchers associated with the Cowles Commission faced while establishing a mathematically and abstractly driven definition of "theory" for Economics. My objective is twofold. First, I explain the specific responses, in other words the strategies to these challenges, by relating them to the different positions the scholar network associated with Cowles occupied in the US academic system (from peripheral/dominate to central/dominant). Second, I analyze the impact of these strategies in the discipline of economics. I argue that by establishing a mathematically and abstract-driven definition of theory, the scholars associated with the Cowles Commission set up the foundations of a long-term research project for economics. This project, while abstract in character, allowed an important part of the discipline to cohere around. More concretely, it was critical in forging an articulated response to criticisms about their interest in technical and mathematical problems per se, and it was central to the process of setting the guidelines for a path of knowledge accumulation.
Keywords: 330; Cowles Commission; economy theory